2008
DOI: 10.1158/1055-9965.epi-07-2541
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Outcomes and Health-Related Quality of Life in Adult Childhood Cancer Survivors: A Report from the Childhood Cancer Survivor Study

Abstract: Purpose: Psychological outcomes, health-related quality of life (HRQOL), and life satisfaction are compared between 7,147 adult childhood cancer survivors and 388 siblings from the Childhood Cancer Survivor Study, examining demographic and diagnosis/treatment outcome predictors. Methods: Psychological distress, HRQOL, and life satisfaction were measured by the Brief Symptom Inventory-18, the Medical Outcomes Survey Short Form-36, and Cantril Ladder of Life, respectively. A self-report questionnaire provided de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
421
8
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 390 publications
(476 citation statements)
references
References 46 publications
42
421
8
5
Order By: Relevance
“…siblings) (Stam et al, 2006;Reinfjell et al, 2009;Zeltzer et al, 2009). However, most studies found that on the whole, survivors of childhood cancer fare the same or have a good QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and function well psychologically (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008). Yet, only a few studies had reported results by both parent proxy and adolescent self-report, compared with controls.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…siblings) (Stam et al, 2006;Reinfjell et al, 2009;Zeltzer et al, 2009). However, most studies found that on the whole, survivors of childhood cancer fare the same or have a good QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and function well psychologically (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008). Yet, only a few studies had reported results by both parent proxy and adolescent self-report, compared with controls.…”
Section: Quality Of Lifementioning
confidence: 99%
“…While a number of studies have reported adverse outcomes (Grant et al, 2006;Speechley et al, 2006;Stam et al, 2006;Reinfjell et al, 2009;Gurney et al, 2009;Nathan et al, 2009;Hudson et al, 2003;Mulhern et al, 2004;Oeffinger et al, 2008), others have concluded that QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and psychosocial adjustment (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008) are satisfactory for the majority of long-term childhood cancer survivors. Finally, a few studies have found that the prevalence of depression in survivors of childhood cancer equal that of healthy controls (Gray et al, 1992;Zebrack and Zeltzer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…15 Overall, most survivors function well psychologically but suffer from psychosocial deficits. 13,14,16 Health related quality of life (HR-QOL) is often normal or even better than standardized norms. 16 However, there may be increased global distress, with issues typically apparent on emotional sub-scales.…”
mentioning
confidence: 99%
“…Prior research has shown that some of the risk factors associated with psychological distress in adult cancer survivors are older age at evaluation, being female, not married, unemployed, having no health insurance, low educational attainment [7,10,26], suffering of cancer-related pain [27,28], and chronic conditions [10,7].…”
Section: Covariates Of Interestmentioning
confidence: 99%